2017
DOI: 10.1016/j.outlook.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Organizational intellectual capital and the role of the nurse manager: A proposed conceptual model

Abstract: The Gilbert Conceptual Model of Organizational Intellectual Capital advances the propositions of human capital theory and social capital theory and is the first model to conceptualize the direct and moderating effects that nurse leaders have on the human capital and social capital of the teams they lead. This model provides a framework for further empirical study and may have implications for practice, organizational policy, and education related to nursing leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…TA B L E 2 Baseline values (least square mean), between-group (control -intervention) differences at follow-up (6 and 12 months), and within group (0-6 months, 6-12 months, and 0-12 months) differences for bonding, linking A, and linking B social capital Although the present intervention was coined as a participatory organizational intervention, the distant leaders and top-level TA B L E 3 Baseline values (least square mean), between-group (control -intervention) differences at follow up (6 and 12 months), and within-group (0-6 months, 6-12 months, and 0-12 months) differences for organizational readiness for change (ORC) and (d) improving teamwork and mutual support in the proper use of assistive devices, relied on the managers to support the workers in prioritizing time for implementing these. In fact, the nurse manager role has been identified as a key role to organizational success and can have profound impact on influencing productivity and financial stability, quality of patient care, job satisfaction, and organizational commitment (Cathcart & Greenspan, 2012;Chase, 2012;Gilbert, Von Ah, & Broome, 2017;Wendler, Olson-Sitki, & Prater, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 2 Baseline values (least square mean), between-group (control -intervention) differences at follow-up (6 and 12 months), and within group (0-6 months, 6-12 months, and 0-12 months) differences for bonding, linking A, and linking B social capital Although the present intervention was coined as a participatory organizational intervention, the distant leaders and top-level TA B L E 3 Baseline values (least square mean), between-group (control -intervention) differences at follow up (6 and 12 months), and within-group (0-6 months, 6-12 months, and 0-12 months) differences for organizational readiness for change (ORC) and (d) improving teamwork and mutual support in the proper use of assistive devices, relied on the managers to support the workers in prioritizing time for implementing these. In fact, the nurse manager role has been identified as a key role to organizational success and can have profound impact on influencing productivity and financial stability, quality of patient care, job satisfaction, and organizational commitment (Cathcart & Greenspan, 2012;Chase, 2012;Gilbert, Von Ah, & Broome, 2017;Wendler, Olson-Sitki, & Prater, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a paucity of studies that focus on the relationships between Social Capital and research utilization, other studies have demonstrated positive relationships between Social Capital and turnover intent, nursing unit effectiveness, and nurse perception of quality of care (Laschinger, Read, Wilk, & Finegan, ; Shin & Lee, ). Nurse leaders influence the creation of Social Capital in the complex nursing work environment through creating structures and processes that allow for nurses to access, exchange, and synthesize information both within and among teams to improve patient and organizational outcomes (Gilbert, Von Ah, & Broome, ). Intentional creation of social networks may increase EBP dissemination and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Yet studies globally document limited genomic nursing competency (Calzone et al, 2014; Godino et al, 2013; Skirton et al, 2012; Seven et al, 2015). Perhaps even more alarming is emerging evidence that for nursing faculty, genomic knowledge is limited and is similar to the students they teach (Donnelly et al, 2017; Read and Ward, 2016).…”
Section: Introductionmentioning
confidence: 99%